Lila and Hadley - Keplinger, Kody (Scholastic Press, 2020)
Hadley is an angry girl: angry at her mother for embezzling money, angry at her estranged older sister, Beth, whom she has to live with while her mother is in jail, angry at having to move to Kentucky away from her friends, and angry at the world because she has retinitis pigmentosa and is slowly going blind; but then she meets Lila, a rescued pit bull who has not responded to anyone else--so if Hadley can train Lila, maybe the dog can get adopted into her forever home, and just maybe Lila can help Hadley deal with her own problems.